LaSrMnO4: Reversible Electrochemical Intercalation of Fluoride Ions in the Context of Fluoride Ion Batteries - Anji Munnangi (Chemistry of Materials, 2017)
This article reports on the investigation of LaSrMnO4 with K2NiF4 type structure for use as an intercalation based high voltage cathode material with high capacity for fluoride ion batteries (FIBs). Charging was performed against PbF2 based anodes and shows that fluoride intercalation proceeds stepwise to form LaSrMnO4F and LaSrMnO4F2–x. Ex-situ X-ray diffraction experiments were recorded for different cutoff voltages for a deeper understanding of the charging process, highlighting additional potential of the method to be used to adjust fluorine contents more easily than using conventional fluorination methods. A discharging capacity of approximately 20–25 mAh/g was found, which is ∼4–5 times higher compared to what was reported previously on the discharging of BaFeO2.5/BaFeO2.5F0.5, approaching discharge capacities for conversion based fluoride ion batteries. Density functional theory based calculations confirm the observed potential steps of approximately 1 and 2 V for the first (LaSrMnO4 → LaSrMnO4F) and second (LaSrMnO4F → LaSrMnO4F2–x) intercalation steps against Pb-PbF2, respectively. Additionally, a detailed structure analysis was performed for chemically prepared LaSrMnO4F2–x (x ∼ 0.2), showing strong similarity to the product which is obtained after charging the batteries to voltages above 2 V against Pb-PbF2. It was observed that charging and discharging kinetics as well as coulomb efficiencies are limited for the batteries in the current state, which can be partly assigned to overpotentials arising from the use of conversion based anode composites and the stability of the charged sample toward carbon black and the current collectors. Therefore, the structural stability of LaSrMnO4F2 on the deintercalation of fluoride ions was demonstrated by a galvanostatic discharging to −3 V against Pb-PbF2, which can be used to compensate such overpotentials, resulting in almost complete recovery of fluorine free LaSrMnO4 with a discharge capacity of ∼100 mAh/g. This is the first report showing that selective extraction of fluoride ions from an oxyfluoride matrix is possible, and it highlights that compounds with K2NiF4 type structure can be considered as interesting host lattices for the reversible intercalation/deintercalation of fluoride ions within intercalation based FIBs.